Aktivitas Kombinasi Krim Daun Pare (Momordica charantia L) dan Kulit Jeruk (Citrus nobilis) dalam Penyembuhan Luka Bakar - I Made Agus Sunadi Putra; Made Dwik Lestari; Ni Nyoman Wahyu Udayani; Ketut Agus Adrianta; Nyoman Budiartha Siada (State University of Gorontalo, 2023)
Burns are injuries to the skin caused by heat, fire, hot steam, exposure to chemicals, solar radiation, or electric shock. Burns need to be treated immediately because they can cause infection in the skin. Healing burns can be done by utilizing several types of existing plants, namely bitter melon leaves and orange peels which are known to be able to help heal burns because they contain secondary metabolites such as flavonoids, tannins, saponins, steroids, alkaloids, and terpenoids which can be used for wound healing. The purpose of this study was to determine the effect of a combination of bitter melon leaf extract cream and orange peel as healing burns in white rats. This research is a quantitative study using laboratory experimental methods with a post test only control group design. In this study, male white rats were made with wounds on the back skin. Using 20 white rats divided into 5 different treatment groups. The negative control was given a cream base, the positive control was given Burnazin cream, F1 3% : 5%, F2 ie 4% : 4%, F3 ie 5% : 3%. The wound was smeared with preparations according to group division and carried out for 14 days. Based on the results of observations of the effect of a combination of bitter melon leaf extract and orange peel cream at F1 concentrations with a concentration ratio of 3%: 5%, it has a faster healing effect on burn area. Based on the results of the Kruskal wallis test on the healing of second degree burns in male white rats, there was a significant difference. The p value or sig is 0.014, so it can be concluded that there is a significant difference between the healing areas of burns in white rats.